2019
DOI: 10.1021/acsami.8b16048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Thermal and Radiation-Induced Chemistries in a Model Organotin Photoresist

Abstract: Organotin photoresists have shown promise for next-generation lithography because of their high extreme ultraviolet (EUV) absorption cross sections, their radiation sensitive chemistries, and their ability to enable highresolution patterning. To better understand both temperatureand radiation-induced reaction mechanisms, we have studied a model EUV photoresist, which consists of a charge-neutral butyl−tin cluster. Temperature-programmed desorption (TPD) showed very little outgassing of the butyl−tin resist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 45 publications
(118 reference statements)
5
53
0
Order By: Relevance
“…To achieve sufficient photon absorption in thin films, and potentially higher etch resistance, metal-containing photoresist materials have been proposed as alternatives. [7][8][9][10][11][12][13] An example of an organometallic photoresist material is the tin-oxo cage (see Fig. 1), 14,15 first described by Puff and Reuter in 1989.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve sufficient photon absorption in thin films, and potentially higher etch resistance, metal-containing photoresist materials have been proposed as alternatives. [7][8][9][10][11][12][13] An example of an organometallic photoresist material is the tin-oxo cage (see Fig. 1), 14,15 first described by Puff and Reuter in 1989.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, MS was also applied to investigate the electron-induced chemistry of Sn oxoclusters as an example of metal-containing molecular resist. 9,23 In these studies, electron-stimulated desorption (ESD) experiments revealed that 80 eV electrons can induce fragmentation of ligands from the clusters and showed how the structure of the cluster affects the efficiency for removal of particular ligands upon electron impact. 23 As a novel example of metal-oxoclusters, Zn-tetranuclear oxoclusters surrounded by trifluoroacetate (TFA) and methacrylate (MA) ligands (Zn(MA)(TFA)) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 9,23 In these studies, electron-stimulated desorption (ESD) experiments revealed that 80 eV electrons can induce fragmentation of ligands from the clusters and showed how the structure of the cluster affects the efficiency for removal of particular ligands upon electron impact. 23 …”
Section: Introductionmentioning
confidence: 99%
“…During the scattering, more molecules can be ionized so that secondary electrons are generated, which have a broad distribution of kinetic energies in the 0-80 eV range. 14 Therefore, the chemistry induced by EUV photons is the result of the electron-induced chemistry [17][18][19] and the chemical a Advanced Research Center for Nanolithography, Science Park 106, processes that the ionized molecules undergo. Furthermore, the probability of absorbing EUV photons by molecules is mainly determined by their elemental composition rather than by the selection rules based on the characteristics of the frontier molecular orbitals that apply in photochemistry.…”
Section: Introductionmentioning
confidence: 99%